A national profile of the impact of parental cancer on their children in Japan. Issue 6 (December 2015) - Inoue, Izumi; Higashi, Takahiro; Iwamoto, Momoko; Heiney, Sue P.; Tamaki, Tomohiro; Osawa, Kaori; Inoue, Miho; Shiraishi, Keiko; Kojima, Rebekah; Matoba, Motohiro
Highlights: Cancer among parents who have dependent children is becoming an increasing problem in Japan due to families postponing parenthood in addition to high lifetime cancer risk. We estimated the national incidence of cancer patients who have minor children in Japan. Substantial numbers of parents are newly diagnosed with cancer every year. More attention should be paid to them both at clinical and policy level. Abstract: Objective: Dependent children under the age of 18 are particularly vulnerable to the stress of parental death from cancer or of having a parent diagnosed and treated for the disease. More and more Japanese couples are postponing parenthood, which increases their chances of developing cancer while they still have a dependent child. However, the problem has not received enough attention from healthcare professionals and policy-makers because the extent and breadth of the problem has never been examined in the Japanese population. Therefore, we aimed to estimate the nationwide incidence of cancer patients who have children under the age of 18 years, as well as the incidence of children who have a parent diagnosed with cancer in Japan. Study design: We calculated the proportion of patients who have children stratified by age, gender and cancer type using electronic medical records of cancer patients (20–59 years old) admitted to the National Cancer Center Hospital (NCCH) for the first time between January 2009 and December 2013. We projected these estimates onto the Japanese population using 2010 population-based cancer registry data, and repeated the projection using 2011 hospital-based cancer registry data so that estimates of patients receiving care at Designated Cancer Care (DCC) hospitals could be obtained. Results: We found that an estimated 56, 143 cancer patients who have 87, 017 dependent children are diagnosed with cancer every year in Japan. The proportion of children in Japan who had a parent newly diagnosed with cancer in 2010 was approximately 0.38%. We estimated that in 2011 there were on average about 82 cancer patients with minor children and 128 minor children who have at least one parent diagnosed with cancer in every DCC hospital in Japan. Conclusion: Parental cancer is common. We have identified that many adults diagnosed with cancer have the double burden of coping with the diagnosis and treatment as well as supporting their children through this experience. Additional data on socioeconomic characteristics and needs assessment of these patients are required to understand how best to help children and families cope with cancer.